Three Continents, one Language: Studying English in a Portuguese Landscape (Brazil, Cape Verde and Portugal) - Azuaga, Luísa (2013)
Unlike other languages, English has spread to all continents and become a truly global language, a process observable in countries, like Brazil, Cape Verde, and Portugal, located in three different continents, and sharing a common official language: Portuguese. This relatively recent development has contributed to the wide exposure to English and the growing influence of the language in their societies, being used with lingua franca communicative purposes, which raises pedagogical issues. Our aim is to map the exposure and use of English as a Lingua Franca in these Portuguese speaking countries through a comparative study of the results from three case studies (Berto 2009, Cavalheiro 2008 and Nunes 2010). By taking into consideration the findings from questionnaires answered by students and teachers of English, it compares and contrasts the respondents’ opinions on the profile of English teachers — native vs. non-native —, the varieties of English to be taught, and the language teaching resources available. In addition, it explores the learners’ interests, motives and purposes in relation to English and the potential communicative interactions between all speakers, so as to better understand ELF in English language education, and how these factors affect or should affect pedagogical practices in a Portuguese environment.